Mean Platelet Volume as A Marker of Thrombosis Event in Antiphospholipid Syndrome Patients - Michael Dwinata; Jonathan H. Haposan; Inolyn Pandjaitan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Antiphospholipid antibody syndrome (APS) is a systemic autoimmune disease associated with venous and/or arterial thrombosis with the presence and persistence of antiphospholipid antibodies (aPL). One of the currently discussed markers related to a high risk of thromboembolism is increased Mean Platelet Volume (MPV). This study aimed to know whether an association exists between MPV and thrombosis event in APS patients. We systematically searched and reviewed studies from MEDLINE, Science Direct and the Cochrane Controlled Trials registry (CENTRAL) from October until November 2018. We use appraisal tools from Critical Appraisal Skills Programme (CASP-UK) for cohort studies. We found two relevant studies to be included in our review.In total, 389 patients consisting 92 APS patient and 297 APS-negative and healthy controls were included. In two studies, the mean of MPV in APS group with thrombosis ranged from 7.85 to 9.22 fl. MPV in APS group with thrombosis was higher than in the APS group without thrombosis and in healthy controls. The platelet size, measured as MPV, reflects platelet reactivity, including aggregation, glycoprotein IIb-IIIa expression and production of more thrombogenic factors. In summary, MPV has a positive correlation with thrombosis event in APS patient. MPV may also be a potential clinical predictor for recurrence of thrombosis in APS patient. We urge that more future prospective studies with larger sample size to be done in order to validate this potential marker.Keywords : Mean platelet volume, thrombosis, antiphospholipid syndrome